MYCN controls an alternative RNA splicing program in high-risk metastatic neuroblastoma. Issue 2 (28th February 2016) - Zhang, Shile; Wei, Jun S.; Li, Samuel Q.; Badgett, Tom C.; Song, Young K.; Agarwal, Saurabh; Coarfa, Cristian; Tolman, Catherine; Hurd, Laura; Liao, Hongling; He, Jianbin; Wen, Xinyu; et al.
Highlights: A characteristic isoform expression pattern is detected in MYCN -amplified NBL tumors. Several splicing factors control the splicing program in NBL tumors. MYCN directly controls the expression of splicing factors PTBP1 and HNRNPA1. Splicing factors PTBP1 and HNRNPA1 and their downstream splicing target PKM2 affect MYCN -amplified NBL cell proliferation. Abstract: The molecular mechanisms underlying the aggressive behavior of MYCN driven neuroblastoma (NBL) is under intense investigation; however, little is known about the impact of this family of transcription factors on the splicing program. Here we used high-throughput RNA sequencing to systematically study the expression of RNA isoforms in stage 4 MYCN -amplified NBL, an aggressive subtype of metastatic NBL. We show that MYCN- amplified NBL tumors display a distinct gene splicing pattern affecting multiple cancer hallmark functions. Six splicing factors displayed unique differential expression patterns in MYCN -amplified tumors and cell lines, and the binding motifs for some of these splicing factors are significantly enriched in differentially-spliced genes. Direct binding of MYCN to promoter regions of the splicing factors PTBP1 and HNRNPA1 detected by ChIP-seq demonstrates that MYCN controls the splicing pattern by direct regulation of the expression of these key splicing factors. Furthermore, high expression of PTBP1 and HNRNPA1 was significantly associated with poor overall survival of stage4 NBL patients ( p ≤ 0.05). Knocking down PTBP1, HNRNPA1 and their downstream target PKM2, an isoform of pro-tumor-growth, result in repressed growth of NBL cells. Therefore, our study reveals a novel role of MYCN in controlling global splicing program through regulation of splicing factors in addition to its well-known role in the transcription program. These findings suggest a therapeutically potential to target the key splicing factors or gene isoforms in high-risk NBL with MYCN- amplification.